Diagnostic Value of Chest Ultrasound in Detecting Complicating Pneumonia in Comparison to CT scan - Abdel-Rahem Rezk, Yasser Farouk; Ali Hassan, Fatma Abdel-Fatah; Youssif, Sahar Farghly; Aboud Salem, Dhekra Ashour; M. Aboelela, Mohamed Gamil (Journal of Neonatal Surgery, 2025)
Introduction: Lung diseases are the most prevalent condition in pediatric medicine. While chest X-rays are typically the initial imaging method used to assess chest diseases, thoracic computed tomography (CT) is regarded as the gold standard for diagnosing and monitoring chest opacities and masses. Chest ultrasound, on the other hand, offers a valuable complementary diagnostic tool. It is widely available, quick, free of radiation, repeatable, and cost-effective, making it highly accurate for detecting chest lesions. Objective: To assess the accuracy of chest ultrasound for diagnosis of complicated pneumonia among kids in comparison to the gold standard (chest CT scan). Methods: This observational, cross-sectional investigation has been conducted in Assiut University Children’s Hospital. This study included 114 patients with symptoms and signs of complicated pneumonia who admitted in ER & pulmonology unit during the period from 1st of January 2021 to thirty-one of August 2022 but others who diagnosed with Acute simple pneumonia were excluded. Results: It was found that LUS had 99%, 88.6%, 91% and 99.2% overall accuracy for diagnosis of pleural effusion, lung abscess, cavitary lesions and necrotizing pneumonia respectively. LUS is able to detect additional findings which couldn't be detected by chest CT, in form of complex septated effusion, empyema and complex non septated in 21 (36.2%) ,10 (17.2%) and 8(13.8%) patients respectively. Conclusion: The application of ultrasound has proven useful in diagnosis of complication of pneumonia in children with the significant advantage of not utilizing ionizing radiation